2003
DOI: 10.1016/s0006-3495(03)74543-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Proteins Alter Nucleotide Binding to Acto-Myosin of Sliding Filaments in Motility Assays

Abstract: The sliding speed of unregulated thin filaments in motility assays is only about half that of the unloaded shortening velocity of muscle fibers. The addition of regulatory proteins, troponin and tropomyosin, is known to increase the sliding speed of thin filaments in the in vitro motility assay. To learn if this effect is related to the rate of MgADP dissociation from the acto-S1 cross-bridge head, the effects of regulatory proteins on nucleotide binding and release in motility assays were measured in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
43
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 54 publications
(83 reference statements)
10
43
2
Order By: Relevance
“…It has been suggested that thin filament FHC mutant proteins (such as the Arg-92 hot spots) markedly alter the nature of the interaction between actin and myosin (16). Consequently, the changes in cooperativity observed in the Arg-92 hot spots may be indicative of alterations in the allosteric regulation of Tm by Tn, whereby the cooperative interactions of Tn-Tm may produce structural changes allowing for strong actin-myosin binding (the transition to "open" state in the three-state model of myofilament activation) (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that thin filament FHC mutant proteins (such as the Arg-92 hot spots) markedly alter the nature of the interaction between actin and myosin (16). Consequently, the changes in cooperativity observed in the Arg-92 hot spots may be indicative of alterations in the allosteric regulation of Tm by Tn, whereby the cooperative interactions of Tn-Tm may produce structural changes allowing for strong actin-myosin binding (the transition to "open" state in the three-state model of myofilament activation) (14).…”
Section: Resultsmentioning
confidence: 99%
“…Regulated in Vitro Motility Assay-Motility assay procedures and measurement were performed as described previously (14). In brief, a nitrocellulose-coated coverslip was attached to a glass microscope slide using double-faced tape, forming a flow cell chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The dialyzed Tn and Tm were then used to produce reconstituted thin filaments (RTF) under rigor conditions (i.e. in the absence of ATP) within the flow cell used for the motility assays (41).…”
Section: Methodsmentioning
confidence: 99%
“…Following this step, 0.35 M Tm and 0.75 M Tn were added and allowed to incubate in the flow cell for 7 min, resulting in the formation of RTF. This method, which had been used previously, creates RTF capable of fully regulating the actomyosin interaction, as evidenced by the lack of filament movement at pCa levels above 9, while also showing a strong Ca 2ϩ -dependent increase in velocity, from pCa ϳ7 to 4 (41). A solution containing 100 nM excess Tn and Tm was also added to the final assay buffer to ensure full and complete activation regulation of the RTFs as described previously (41,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation